Pengaruh Gross Profit Margin (GPM) terhadap Harga Saham PT Gudang Garam TBK - Rusman Rusman; Nafisah Nurulrahmatia; Muhamad Rimawan (Journal of Islamic Economics and Finance, 2024)
This research aims to determine whether there is an influence of Gross Profit Margin (GPM) on the share price of PT Gudang Garam TBK. The research method used is associative research. The population used in this research is the entire financial report of PT. Gudang Garam Tbk has been listed on the Indonesia Stock Exchange (BEI) for 32 years, from 1990 to 2022. The sample in this research is all of the financial reports of PT. Gudang Garam Tbk. For the 10 year period 2013-2022. The sampling technique used was purposive sampling. The data analysis technique used is simple linear regression analysis and T test with the help of the SPSS Statistics v22 for Windows program. The results of this research show that Gross Profit Margin (GTM) has no effect on share prices at PT. Gudang Garam Tbk.